A hybrid-coated modified graphite negative electrode material, a preparation method thereof and application thereof in high-power batteries
Patent Information
- Application Number
- CN202611223412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]针对现有技术中石墨负极高倍率性能不足的缺陷,本发明提供一种混合包覆层改性石墨负极材料及其制备方法与在大功率电池中的应用
1、本发明利用180℃水热产生的具有高极性的羰基(C=O)和羟基(-OH)中间产物,与石墨表面的活性位点形成强化学键合,实现纳米级均匀包覆。相比传统直接混合包覆方式,水热中间体的界面锚定效应显著提升了包覆层与石墨基体的结合力,避免了包覆不均匀和界面脱粘问题。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a hybrid coating modified graphite anode material, its preparation method, and its application in high-power batteries. Background Technology
[0002] Lithium-ion batteries, with their significant advantages of high energy density and long cycle life, have been widely used in many fields such as consumer electronics, electric vehicles, and energy storage systems. As application scenarios continue to expand, the requirements for high-rate performance (i.e., high-current charge and discharge capability) of lithium batteries are increasing—especially in fields such as start-stop power supplies, drones, data center backup power supplies, power tools, and e-cigarettes, where batteries need to withstand high-current discharge of 10~100C.
[0003] As the mainstream anode material for commercial lithium-ion batteries, graphite has a high theoretical capacity of 372 mAh / g and excellent cycle stability. However, due to its inherent defects of insufficient electronic conductivity and low lithium-ion diffusion rate, it is prone to problems such as increased polarization and rapid capacity decay in high-rate charge and discharge scenarios, making it difficult to meet the actual needs of high-current discharge.
[0004] To overcome the bottleneck of graphite's high-rate performance, surface coating modification has become a common approach in existing technologies. For example, while soft carbon generated by heat treatment after pitch coating can effectively improve electronic conductivity, its interlayer spacing is small (approximately 0.34~0.35 nm), limiting its promotion of lithium-ion transport. While coating with metal oxides can optimize lithium-ion diffusion efficiency, it may lead to a decrease in electronic conductivity. Furthermore, in existing hard carbon coating technologies, the hard carbon precursor is directly mixed with graphite before carbonization, often resulting in uneven coating and weak interfacial bonding, making the modification effect difficult to sustain.
[0005] Therefore, developing a modified graphite anode material that combines high electronic conductivity with high lithium-ion migration rate has become a key issue that urgently needs to be addressed in the current lithium-ion battery field, and it has important theoretical and application value. Summary of the Invention
[0006] To address the shortcomings of existing graphite anodes in terms of insufficient high-rate performance, this invention provides a hybrid coated layer modified graphite anode material, its preparation method, and its application in high-power batteries. This invention pre-constructs a functionally rich "interface anchoring layer" on the graphite surface using a hydrothermal intermediate, which then evolves into a highly efficient ion diffusion channel during subsequent high-temperature treatment, significantly improving the high-current discharge capability of the graphite anode material at 10~100C.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A hybrid coated modified graphite anode material includes a graphite matrix, the surface of which is coated with a hard carbon layer formed by the pyrolysis of a sucrose hydrothermal intermediate. The thickness of the hard carbon layer is 10~50 nm; The interlayer spacing d002 of the hard carbon layer is 0.385~0.410 nm; The carbonyl group (C=O) in the hard carbon layer has an atomic percentage content of 1.5% to 3.0%, and the ether bond (COC) has an atomic percentage content of <0.1%.
[0008] Furthermore, the particle size of the graphite matrix is 5~20μm.
[0009] A method for preparing a mixed-coating modified graphite anode material includes the following steps: Step 1, hydrothermal intermediate synthesis: sucrose and deionized water are mixed at a mass ratio of 1:2 to 1:5 and reacted in a high-pressure reactor at 180°C for 1.5 to 4 hours. The reaction pressure is controlled at 1.0 to 2.5 MPa to obtain a brown intermediate slurry containing carbonyl, hydroxyl and furan structures. Step 2, in-situ adsorption and coating: The graphite matrix is added to the intermediate slurry obtained in step (1), wherein the mass ratio of the graphite matrix to the hydrothermal intermediate in terms of solid content is 30:1 to 50:1, and the mixture is sheared and stirred at a speed of 500 to 1500 r / min for 2 to 6 hours to form a uniform suspension. Step 3, gradient drying: The suspension obtained in step (2) is dried at 60~120℃ for 6~12h to fully remove the solvent; Step 4, segmented gradient carbonization: segmented carbonization is carried out under inert gas protection, with an inert gas flow rate of 50~200mL / min; First stabilization stage: Heat to 400-600℃ at a heating rate of 2-5℃ / min, and hold at that temperature for 2 hours; The second stage of hard carbon forming: continue to heat to 1000~1500℃ and hold at that temperature for 2~6 hours; Naturally cooled to room temperature, a mixed-coated modified graphite anode material was obtained.
[0010] Furthermore, the inert gas mentioned in step 4 is nitrogen or argon.
[0011] A high-power lithium battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode is a negative electrode sheet prepared by a mixed coating layer modified graphite negative electrode material.
[0012] Furthermore, the lithium battery can achieve a discharge rate of 10~100C.
[0013] Furthermore, the lithium battery retains ≥80% of its capacity after 500 cycles under 1C charging / 40C discharging conditions.
[0014] Furthermore, the initial coulombic efficiency of the hybrid coated modified graphite anode material is ≥90%.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes highly polar carbonyl (C=O) and hydroxyl (-OH) intermediates generated by hydrothermal treatment at 180℃ to form strong chemical bonds with active sites on the graphite surface, achieving uniform nanoscale coating. Compared to traditional direct mixing coating methods, the interfacial anchoring effect of the hydrothermal intermediates significantly enhances the bonding force between the coating layer and the graphite matrix, avoiding problems such as uneven coating and interfacial debonding.
[0016] 2. This invention utilizes specific oxygen-containing functional groups (C=O) in hydrothermal products as a "structural scaffold," inducing isotropic bending and closed pores in the carbon layer during carbonization at 1000~1500℃, thereby expanding the interlayer spacing to 0.385~0.410 nm. Compared to traditional soft carbon coating of pitch (interlayer spacing of only 0.34~0.35 nm), this significantly reduces the resistance to lithium ion migration and constructs isotropic fast ion channels.
[0017] 3. This invention utilizes a segmented heat treatment process to completely remove unstable ether bonds (COC) that lead to low initial coulombic efficiency while retaining beneficial carbonyl groups (C=O), thus maintaining the initial coulombic efficiency of the composite material above 90%. Comparative data show that without segmented carbonization, the residual amount of ether bonds is significantly increased, and the initial coulombic efficiency is significantly reduced.
[0018] 4. The hard carbon layer in the hybrid layer has isotropic fast ion channels, which significantly reduces electronic contact resistance and ion migration resistance, enabling high-current discharge of 10~100C. Example data shows that the material of this invention achieves a capacity retention of 82.1%~86.8% after 500 cycles under extreme conditions of 1C charging / 40C discharging.
[0019] 5. Thanks to the nanoscale uniform coating achieved by the interfacial anchoring effect of the hydrothermal intermediate, and the buffering effect of the hard carbon layer on volume changes, the cycle stability of the modified graphite anode material of this invention is significantly better than that of traditional coating schemes. In the examples, the capacity retention rate can reach 89.7%~91.5% after 3000 cycles of 1C charge / 1C discharge. Detailed Implementation
[0020] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below.
[0021] Example 1: Preparation process parameters: (1) Hydrothermal intermediate synthesis: Sucrose and deionized water were mixed at a mass ratio of 1:3 and reacted in a high-pressure reactor at 180℃ and 1.8MPa for 2.5h to obtain a brown intermediate slurry.
[0022] (2) In-situ adsorption and coating: Take a graphite matrix with a particle size of 10 μm and add it to the above intermediate slurry. The mass ratio of graphite matrix to hydrothermal intermediate (based on solid content) is 40:1. Shear and stir at 800 r / min for 4 h to form a uniform suspension.
[0023] (3) Gradient drying: The suspension is dried at 80°C for 8 hours.
[0024] (4) Segmented gradient carbonization: Carbonization is carried out under a nitrogen atmosphere with a nitrogen flow rate of 100 mL / min; the temperature is increased to 500℃ at 3℃ / min and held for 2 hours; the temperature is further increased to 1300℃ and held for 4 hours; and then naturally cooled to room temperature.
[0025] Material structural characteristics: The coating layer is 30 nm thick, the interlayer spacing d002 = 0.395 nm, the carbonyl (C=O) atomic percentage is 2.2%, and the ether bond (COC) content is 0.06%.
[0026] Battery performance test data: First-time coulomb efficiency: 94.2%; Capacity retention after 3000 1C charge / 1C discharge cycles: 91.5%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 86.8%.
[0027] Example 2: Preparation process parameters: (1) Hydrothermal intermediate synthesis: Sucrose and deionized water were mixed at a mass ratio of 1:2 and reacted in a high-pressure reactor at 180℃ and 1.0MPa for 1.5h to obtain a brown intermediate slurry.
[0028] (2) In-situ adsorption and coating: Take a graphite matrix with a particle size of 5 μm and add it to the above intermediate slurry. The mass ratio of graphite matrix to hydrothermal intermediate (based on solid content) is 50:1. Shear and stir at 1500 r / min for 2 h to form a uniform suspension.
[0029] (3) Gradient drying: The suspension was dried at 120℃ for 6 hours.
[0030] (4) Segmented gradient carbonization: Carbonization is carried out in an argon atmosphere with an argon flow rate of 50 mL / min; the temperature is increased to 600℃ at 5℃ / min and held for 2 hours; the temperature is further increased to 1500℃ and held for 2 hours; and then naturally cooled to room temperature.
[0031] Material structural characteristics: The coating layer is 15 nm thick, the interlayer spacing d002 = 0.410 nm, the carbonyl (C=O) atomic percentage is 1.8%, and the ether bond (COC) content is 0.04%.
[0032] Battery performance test data: First-time coulomb efficiency: 93.5%; Capacity retention after 3000 1C charge / 1C discharge cycles: 90.2%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 85.3%.
[0033] Example 3: Preparation process parameters: (1) Hydrothermal intermediate synthesis: Sucrose and deionized water were mixed at a mass ratio of 1:5 and reacted in a high-pressure reactor at 180℃ and 2.5MPa for 4 hours to obtain a brown intermediate slurry.
[0034] (2) In-situ adsorption and coating: Take a graphite matrix with a particle size of 20 μm and add it to the above intermediate slurry. The mass ratio of graphite matrix to hydrothermal intermediate (based on solid content) is 30:1. Shear and stir at 500 r / min for 6 h to form a uniform suspension.
[0035] (3) Gradient drying: The suspension was dried at 60°C for 12 hours.
[0036] (4) Segmented gradient carbonization: Carbonization is carried out under a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min; the temperature is increased to 400℃ at 2℃ / min and held for 2 hours; the temperature is further increased to 1000℃ and held for 6 hours; and then naturally cooled to room temperature.
[0037] Material structural characteristics: The coating layer is 45 nm thick, the interlayer spacing d002 = 0.385 nm, the carbonyl (C=O) atomic percentage is 2.8%, and the ether bond (COC) content is 0.09%.
[0038] Battery performance test data: First-time coulomb efficiency: 92.8%; Capacity retention after 3000 1C charge / 1C discharge cycles: 89.7%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 82.1%.
[0039] Comparative Example 1 (Traditional asphalt soft carbon coating): Preparation process: Using existing asphalt coating technology, the mass ratio of asphalt to graphite is 5:95, and direct carbonization is carried out at 1000℃ in a nitrogen atmosphere for 4 hours, without hydrothermal intermediate treatment steps or segmented carbonization steps.
[0040] Material structural characteristics: The coating layer is soft carbon with an interlayer spacing of d002=0.345nm, no obvious C=O functional groups, and a COC content of 0.52%.
[0041] Battery performance test data: First-time coulomb efficiency: 86.7%; Capacity retention after 3000 1C charge / 1C discharge cycles: 75.3%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 58.2%.
[0042] Comparative Example 2 (no hydrothermal intermediate treatment, direct sucrose coating): Preparation process: The hydrothermal intermediate synthesis step was omitted, and sucrose and graphite were directly mixed in the proportion of Example 1. The subsequent drying and carbonization processes were completely consistent with those of Example 1.
[0043] Material structural characteristics: The coating layer is uneven, with a thickness fluctuating from 20 to 60 nm. The interlayer spacing d002 = 0.362 nm, the percentage of C=O atoms is 0.8%, and the COC content is 0.35%.
[0044] Battery performance test data: First-time coulomb efficiency: 88.5%; Capacity retention after 3000 1C charge / 1C discharge cycles: 78.6%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 65.7%.
[0045] Comparative Example 3 (non-segmented carbonization, direct high-temperature calcination): Preparation process: The hydrothermal intermediate synthesis, in-situ adsorption coating, and gradient drying processes were completely consistent with those in Example 1. The carbonization step was changed to directly heating to 1300℃ at a nitrogen flow rate of 100mL / min and holding at that temperature for 6 hours, without a low-temperature stabilization stage.
[0046] Material structural characteristics: The coating thickness is 28 nm, the interlayer spacing d002 = 0.378 nm, the percentage of C=O atoms is 0.5%, and the COC content is 0.28%.
[0047] Battery performance test data: First-time coulomb efficiency: 90.1%; Capacity retention after 3000 1C charge / 1C discharge cycles: 82.4%; Capacity retention after 500 cycles of 1C charge / 40C discharge: 72.3%.
[0048] Performance testing: The negative electrode materials of Examples 1-3 and Comparative Examples 1-3 were mixed with CMC, SBR, and conductive agent in a mass ratio of 95:2:1.5:1.5, and coated onto copper foil to form a negative electrode sheet. This sheet was then combined with the positive electrode (lithium iron phosphate), a separator, and an electrolyte (1.5 mol / L). The cells were assembled into a 40135-10Ah cylindrical battery, and their electrochemical performance was tested.
[0049] The test results are shown in the table below:
[0050] Test conclusion: (1) The modified graphite anode materials of Examples 1-3 of the present invention all maintained an initial coulombic efficiency of over 92%, which is much higher than that of the comparative examples. The core reason is that the segmented carbonization process completely removed the unstable ether bonds (COC<0.1%), retained the beneficial carbonyl groups, and eliminated the side reaction active sites.
[0051] (2) The cycling performance of the embodiment under high-rate discharge (40C) is particularly improved, with a capacity retention of ≥82% after 500 cycles, which is up to 49.1% higher than that of Comparative Example 1. This is due to the hard carbon layer induced by the hydrothermal intermediate having a wide interlayer spacing of 0.385~0.410nm, which constructs an isotropic fast ion channel and reduces ion migration resistance.
[0052] (3) Under conventional multiplication rate (1C), the capacity retention rate of the Example 3000 cycles was close to 90% or above, which was significantly better than that of the comparative examples, proving that the interface anchoring effect of the hydrothermal intermediate achieved nanoscale uniform coating and improved the structural stability of the material.
[0053] (4) The performance degradation of Comparative Examples 1-3 verified the technical defects of traditional soft carbon coating layers, such as small spacing, uneven coating without hydrothermal intermediate treatment, and incomplete removal of non-segmented carbon ether bonds. This proved that the synergistic effect of the three major innovations of this invention—hydrothermal intermediate induction, micro-control of hard carbon layer, and segmented heat treatment to optimize the first efficiency—is the key to improving the high-rate performance of graphite anodes.
[0054] Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this invention without departing from the spirit and scope of the technical solutions of this invention, and all such modifications or substitutions should be covered within the scope of the claims of this invention.
Claims
1. A mixed-coating modified graphite anode material, characterized in that, Includes a graphite matrix, the surface of which is coated with a hard carbon layer formed by the pyrolysis of a sucrose hydrothermal intermediate; The thickness of the hard carbon layer is 10~50 nm; The interlayer spacing d002 of the hard carbon layer is 0.385~0.410 nm; The carbonyl group (C=O) in the hard carbon layer has an atomic percentage content of 1.5% to 3.0%, and the ether bond (COC) has an atomic percentage content of <0.1%.
2. The hybrid coated layer modified graphite anode material according to claim 1, characterized in that, The particle size of the graphite matrix is 5~20μm.
3. A method for preparing a mixed-coating modified graphite anode material as described in claim 1 or 2, characterized in that, Includes the following steps: Step 1, hydrothermal intermediate synthesis: sucrose and deionized water are mixed at a mass ratio of 1:2 to 1:5 and reacted in a high-pressure reactor at 180°C for 1.5 to 4 hours. The reaction pressure is controlled at 1.0 to 2.5 MPa to obtain a brown intermediate slurry containing carbonyl, hydroxyl and furan structures. Step 2, in-situ adsorption and coating: The graphite matrix is added to the intermediate slurry obtained in Step 1. The mass ratio of the graphite matrix to the hydrothermal intermediate, based on the solid content, is 30:1 to 50:
1. The mixture is sheared and stirred at a speed of 500 to 1500 r / min for 2 to 6 hours to form a uniform suspension. Step 3, gradient drying: The suspension obtained in step 2 is dried at 60~120℃ for 6~12h to completely remove the solvent; Step 4, segmented gradient carbonization: segmented carbonization is carried out under inert gas protection, with an inert gas flow rate of 50~200mL / min; First stabilization stage: Heat to 400-600℃ at a heating rate of 2-5℃ / min, and hold at that temperature for 2 hours; The second stage of hard carbon forming: continue to heat to 1000~1500℃ and hold at that temperature for 2~6 hours; Naturally cooled to room temperature, a mixed-coated modified graphite anode material was obtained.
4. The preparation method according to claim 3, characterized in that, The inert gas mentioned in step 4 is nitrogen or argon.
5. A high-power lithium battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator, characterized in that, The negative electrode is a negative electrode sheet prepared from the mixed coating modified graphite negative electrode material as described in claim 1 or 2.
6. The high-power lithium battery according to claim 5, characterized in that, The lithium battery can achieve a discharge rate of 10~100C.
7. The high-power lithium battery according to claim 5, characterized in that, The lithium battery retains ≥80% of its capacity after 500 cycles under 1C charging / 40C discharging conditions.
8. The high-power lithium battery according to claim 5, characterized in that, The initial coulombic efficiency of the hybrid coated modified graphite anode material is ≥90%.